Increasing IPAS Learning Interest through the Discovery Learning Model - safirozahro (Journal of Education and Teaching Learning, 2026)
Social studies learning in elementary school requires the active involvement of students, but in practice students' interest in learning is still often low because learning tends to be teacher-centered. This condition was also found in grade III students of SD Negeri 134II Purwosari who showed low attention, participation, and curiosity in participating in science learning. This research aims to increase interest in learning social studies through the application of the discovery learning model. The method used is Class Action Research which is carried out in two cycles, including the stages of planning, implementation, observation, and reflection. The research subjects amounted to 31 grade III students. Data were collected through observation, questionnaires, and documentation, then analyzed using qualitative and quantitative descriptive techniques. The results of the study show that the application of the discovery learning model  is able to increase students' interest in learning gradually and significantly. In the pre-cycle stage, the average student learning interest was 45 in the low category, increased to 70 in the first cycle with the sufficient category, and reached 85 in the second cycle with the high category. Thus, the discovery learning model  is effective in increasing interest in learning social studies and creating more active, meaningful, and student-centered learning.